Rho Signaling in Synaptic Plasticity, Memory, and Brain Disorders - Zhang, Haorui; Ben Zablah, Youssif; Zhang, Haiwang; Jia, Zhengping (Frontiers in Cell and Developmental Biology, 2021)
Memory impairments are associated with many brain disorders such as autism, Alzheimer's disease, and depression. Forming memories involves modifications of synaptic transmission and spine morphology. The Rho family small GTPases are key regulators of synaptic plasticity by affecting various downstream molecules to remodel the actin cytoskeleton. In this paper, we will review recent studies on the roles of Rho proteins in the regulation of hippocampal long-term potentiation (LTP) and depression (LTD), the most extensively studied forms of synaptic plasticity widely regarded as cellular mechanisms for learning and memory. We will also discuss the involvement of Rho signaling in spine morphology, the structural basis of synaptic plasticity and memory formation. Finally, we will review the association between brain disorders and abnormalities of Rho function. It is expected that studying Rho signaling at the synapse will contribute to the understanding of how memory is formed and disrupted in diseases.